STEPS OF TEACHING STATISTICAL INDICATORS OF ECONOMIC AND SOCIAL GEOGRAPHY (Proceedings of International Educators Conference, 2022)
In the lessons of economic and social geography, students are divided into four stages of developing the skills of calculating, analyzing and interpreting the essence of statistical indicators. The work to be carried out at each stage and their characteristics are explained.